A Participatory GIS-based Multicriteria Decision Analysis Approach to Map the Geospatial Feasibility of Managed Aquifer Recharge in a Tunisian Coastal Watershed - Chekirbane, Anis; Khemiri, Khaoula; Martins, Pedro Tiago; Stefan, Catalin; Panagiotou, Constantinos F. (My University, 2025)
Managed aquifer recharge (MAR) is essential for enhancing groundwater storage and ensuring long-term water sustainability, particularly in semiarid regions. This study focuses on identifying and mapping suitable MAR areas in the Chiba watershed, Tunisia, by integrating hydrogeophysical, hydrological, and socioeconomic criteria. The methodology combines geographical information systems (GISs), multicriteria decision analysis (MCDA), and hydrological modeling. A stakeholder-driven analytical hierarchical process (AHP) is used to assess the MAR suitability criteria. To capture seasonal variability, the feasibility assessment is conducted separately for wet and dry periods. Three thematic layers are considered: the intrinsic hydrogeophysical conditions of the site (IS), water availability (WA), and water demand (WD). The results indicate that water availability is the dominant factor (49.3%), followed by water demand (30%) and site conditions (20%). MAR feasibility maps show that areas classified ‘highly’ to ‘very highly feasible’ represent 19% of the total watershed area. The maps highlight also the coastal areas as highly suitable because of their optimal hydrogeological characteristics, surplus water resources, and high agricultural and ecological demands. In contrast, upstream areas are less feasible because of their limited recharge potential and lower water availability. The maps also suggest specific MAR typologies, such as using treated wastewater in coastal areas and infiltration basins upstream. In conclusion, this study provides a replicable framework for integrating MAR into water policies by aligning site selection with recharge objectives, available water sources, and socioeconomic factors. The findings emphasize the critical role of stakeholder engagement in MAR planning and its embedding in existing water policies, providing a replicable framework for improving groundwater management in semiarid regions.
Keywords: MAR typology; Stakeholder-adapted approach; Analytical hierarchical process; MAR planning; Decision-making